Ład moralny w gospodarce – idea czy rzeczywistość? - Kolasińska, Elżbieta (Acta Universitatis Lodziensis. Folia Sociologica, 2012)
The aim of this study is to attempt to answer the question: Is the moral order in the economy a lofty idea, or necessary, modern practice of action? Depreciation of certain moral values in favor of other implies their diversity, relativism and universality also in the economic sector. Norms and moral obligations, universal values and trust are the intrinsic components of the order in the economy. Moral order is one of the pillars of an efficient economy. Each actor of economic life is a creative individual who should make his/her „brick” in building the common capital – the moral order. It is a „signpost” of economic actors, the pattern of evaluation of good and evil, right and wrong behavior, which also eliminates confusion and reduces the „transaction costs”. Timeless values such as diligence, industriousness, responsibility, kindness, mutuality, honesty are the intrinsic components of the moral order, which is necessary in business. Ignoring the moral norms and relationships in the economy is a risky building on the „dysfunctional foundation” that will bring more harm than good. In Poland, the growing awareness that the moral order in the economy is not only a laudable idea, but the key to its competitiveness, building a positive image.